Perlindungan Hukum Lahan Pertanian Pangan Berkelanjutan (PLP2B) Di Kabupaten Gresik Terhadap Ijin Usaha dan Industri - Muhammad Hamzah Takim* (Universitas Airlangga, 2018)
Rather than the function of agricultural land resulted in a variety of direct and indirect impacts and the serious implications of negative impacts on food production, environment, and culture of society that live on the upstream and surrounding land that is converted The. Thus over the function of agricultural land not only causes food production capacity to fall, but is one form of investment waste, degradation of agroecosystems, degradation of traditions and culture of agriculture, and slowly The perpetrators of the food farming will leave the food sector when not balanced by alihfunction control, incentive giving, and community empowerment. Therefore, the determination of sustainable food farming land and the management of food farming land is one of the very strategic policies.